The importance of the interface in the management of acute respiratory failure - Vojnović Jelena; Hromiš Sanja (Association of Nurses Technicians and Midwives, 2020)
Non-invasive ventilation is a form of mechanical ventilatory support that doesn't require endotracheal intubation of the patient. The interface (mask) is a connection between the device and the patient that allows the set pressure gradient supplied by the ventilator to be transmitted to the airways. Today, there are different types of interfaces, which differ in shape, size, mechanical properties, and comfort. Despite the wide of different mask, common reasons for poor patient adaptation to NIV are related to side effects of the interface such as air loss, skin damage, and mask discomfort. We can prevent these side effects with a basic knowledge of the principles of handling and selecting the optimal interface.